Recent Advancements in Pathogenic Mechanisms, Applications and Strategies for Entomopathogenic Fungi in Mosquito Biocontrol - Yujie Qin; Xiaoyu Liu; Guoxiong Peng; Yuxian Xia; Yueqing Cao (Journal of Fungi, 2023)
Fungal diseases are widespread among insects and play a crucial role in naturally regulating insect populations. Mosquitoes, known as vectors for numerous infectious diseases, pose a significant threat to human health. Entomopathogenic fungi (EPF) have emerged as highly promising alternative agents to chemical mosquitocides for controlling mosquitoes at all stages of their life cycle due to their unique infection pathway through direct contact with the insect’s cuticle. In recent years, significant advancements have been made in understanding the infection pathways and pathogenic mechanisms of EPF against mosquitoes. Various strategies involving the use of EPF alone or combinations with other approaches have been employed to target mosquitoes at various developmental stages. Moreover, the application of genetic technologies in fungi has opened up new avenues for enhancing the mosquitocidal efficacy of EPF. This review presents a comprehensive summary of recent advancements in our understanding the pathogenic mechanisms of EPF, their applications in mosquito management, and the combination of EPF with other approaches and employment of transgenic technologies. The biosafety concerns associated with their use and the corresponding approaches are also discussed. The recent progress suggests that EPF have the potential to serve as a future biorational tool for controlling mosquito vectors.